2000
DOI: 10.1074/jbc.275.4.2676
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of Peptides Targeted to the EF Hands of Calmodulin

Abstract: This report describes the use of the concept of inversion of hydropathy patterns to the de novo design of peptides targeted to a predetermined site on a protein. Eight-and 12-residue peptides were constructed with the EF hands or Ca 2؉ -coordinating sites of calmodulin as their anticipated points of interaction. These peptides, but not unrelated peptides nor those with the same amino acid composition but a scrambled sequence, interacted with the two carboxyl-terminal Ca 2؉ -binding sites of calmodulin as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 67 publications
1
53
0
Order By: Relevance
“…14 We recently described a 12-mer peptide CALP2 with all characteristics necessary to define the role of CaM in the production of radicals by inflammatory cells. 15,16 The peptide binds EF hand motifs of the calcium-binding proteins CaM and troponin C. Moreover, we showed that CALP2 inhibited the action of CaM, 15,17 but increased [Ca 2 þ ] i in airway epithelial cells, the latter being accompanied by an increased NO production by these cells. 18 Moreover, the effects of CALP2 were likely due to the sustained opening of calcium channels present in epithelial cells.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…14 We recently described a 12-mer peptide CALP2 with all characteristics necessary to define the role of CaM in the production of radicals by inflammatory cells. 15,16 The peptide binds EF hand motifs of the calcium-binding proteins CaM and troponin C. Moreover, we showed that CALP2 inhibited the action of CaM, 15,17 but increased [Ca 2 þ ] i in airway epithelial cells, the latter being accompanied by an increased NO production by these cells. 18 Moreover, the effects of CALP2 were likely due to the sustained opening of calcium channels present in epithelial cells.…”
mentioning
confidence: 68%
“…Furthermore, we earlier showed that CALP2 did not bind to CaM in the hydrophobic core, which is typical for W7, 66 but rather interferes with the carboxyl-terminal calcium binding site of CaM. 15 Moreover, it was recently shown that, depending on the protein bound to CaM, CaM undergoes marked different conformational changes, leading to changed calcium-binding. 67 It is therefore assumed that W7 inhibits the action of CALP2 through a different inhibitory mechanism on CaM, leading to altered conformational changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, enhanced affinity by increased reciprocity of the pattern of hydropathy and increased length of the peptide resulted in a change of functional activity. Whereas CALP1 shows biological effects similar to Ca 2ϩ , CALP2 acts as an antagonist for CaM (26). A possible role for Ca 2ϩ influx and CaM activation in Fc⑀RI-induced affinity modulation of VLA-5 for fibronectin combined with the assumption that, based on the pattern of hydropathy, the EF-hand-like domains of VLA-5 are potential binding sites for CALPs suggest several targets for these peptides to interfere with mast cell adhesion.…”
mentioning
confidence: 99%